Systematic assessment of triticale‐based biorefinery strategies: investment decisions for sustainable biorefinery business models. (31st August 2018) - Chambost, Virginie; Janssen, Matty; Stuart, Paul R
Abstract: Strategic investments in biorefinery projects are increasingly being made, and involve non‐traditional decision making, especially considering the technology and market risks involved. From the investor's perspective, the decision‐making process leading to product/process combinations for implementation as a biorefinery to achieve a sustainable business model and good economic returns is not obvious. Typical metrics used for investment decision making have some limitations regarding the recognition of acceptable technology risks relative to economic returns. They often do not appropriately consider factors and analyses related to, for example, environmental impact and the longer term competitive position of new product portfolios. The methodology presented in this article is an approach to identifying a 'practical' set of multi‐disciplinary decision‐making criteria to enable the selection of the preferred product/process biorefinery implementation strategy. The case of investment options in the triticale ( X Triticosecale Wittmack) biorefinery is used as an example. Through this risk‐based methodology, technology risks as well as economic, environmental, and competitive benefits associated with different business model options are identified. This methodology leads to the development of a series of multi‐criteria decision‐making (MCDM) panels to define a set of practical criteria suitable for a final MCDM for the identification of triticale‐based biorefinery alternatives leading to long‐term and sustainable business models. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd